2010
DOI: 10.1089/lap.2009.0269
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Distal Ureterectomy with Boari Flap Reconstruction for Distal Ureteral Urothelial Cancers: A Single Institutional Pilot Experience

Abstract: RDUBF reconstruction is technically feasible with using DSRS in select patients with distal ureteral cancer without disease recurrence in the short term. A larger cohort, with long-term follow-up, is necessary to validate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…Although early reports of the robotic approach have been addressed by others for cases involving malignancy, we have thus far limited our experience to benign indications. 19,20 While we have significant experience with both laparoscopic and robot-assisted urologic procedures, our preferred approach for distal/mid ureteral reimplantation currently favors robotic assistance over pure laparoscopy. We believe the distal ureter dissection and unique angles involved during suturing are aided by robot assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although early reports of the robotic approach have been addressed by others for cases involving malignancy, we have thus far limited our experience to benign indications. 19,20 While we have significant experience with both laparoscopic and robot-assisted urologic procedures, our preferred approach for distal/mid ureteral reimplantation currently favors robotic assistance over pure laparoscopy. We believe the distal ureter dissection and unique angles involved during suturing are aided by robot assistance.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[6][7][8][9][10][11][12][13][14][15][16][17] Rassweiler et al [7] observed longer operative time (253 minutes vs. 220 minutes), shorter hospital stay (8 days vs.17 day) with 100% successs rate in the [11] 1 210 3 90 50 mg morphine…”
Section: Discussionmentioning
confidence: 99%
“…Ramalingam et al [8] Allarpathi et al [15] 2 RALBF UT 1 M 2R 245 2 30 6 22 mg morphine 1F Soares et al [16] 2 H 2F 1R US 1L 120 2 140 6 Gozen et al Ramalingam et al [8] performed laparoscopic ureteral reimplantation with Boari flap in 3 patients successfully with median operative time of 320 mins (range 300-320 min). Castillo et al [9] reported 9 cases of laparoscopic reimplantation procedure with Boari flap.…”
Section: Discussionmentioning
confidence: 99%
“…Schimpf y cols, en el 2008 fueron los primeros en publicar un caso de neoimplante vesicoureteral con técnica de fl ap Boari con asistencia robótica en un caso de estenosis ureteral benigna con resultados muy satisfactorios 19 . En relación a la confección de esta técnica asistida por robot para neoplasias del uréter distal, existen sólo dos casos publicados por Allaparthi y cols, en 2010, con buenos resultados quirúrgicos, aún cuando con se guimiento aún corto 7 . En esta comunicación aportamos un caso adicional a la literatura de ureterectomía distal por tumor de urotelio con neoimplante vesicoureteral según la técnica de Flap Boari asistida por robot da Vinci.…”
Section: Discussionunclassified
“…En el año 2005 presentamos nuestra experiencia inicial con esta técnica laparoscópica en la resolución de lesiones ureterales benignas 4 , y en el año 2008 comunicamos su aplicación en 2 casos de lesiones tumorales de uréter distal 5 . Existen sólo 2 reportes de su uso por vía laparoscópica en cirugía oncológica 5,6 ; sin embargo, a la actualidad han sido comunicado sólo 2 casos de cirugía robótica 7 . Presentamos un caso de carcinoma urotelial del uréter distal al que se le realizó ureterectomía distal con neoimplante vesicoureteral según la técnica de Boari asistida por robot.…”
Section: Introductionunclassified